Efektivitas Ekstrak Bawang Putih terhadap Efek Hepatotoksik Aflatoksin B1 pada Ayam Pedaging Periode Awal - Muspita Dyah Utami, Merry; Agus, Ali; -, Wihandoyo; -, Kurniasih (Jurnal Veteriner; Vol 12, No 3 (2011), 2012)
The aim of this study was to evaluate the effect of garlic extract (GE) in rations on the bloodcholesterol profiles of aflatoxin B-induced hepatotoxic in the early stage of broiler chickens. As many as140 one-day old chicks were used in this study. They were randomly divided into 16 treatment groups andeach group consists of 9 chickens. The experimental design adopted in this study was completely randomizedfactorial design consisting 4 concentrations of aflatoxin (A0 : 0 ppb, A1:500 ppb, A2: 1000 ppb and A3:1500 ppb) and 4 concentrations of garlic extract (B0: 0% B1:2% B2: 4% and B3 6%). The treatment wascarried out for 21 days. The serum levels of total cholesterol, low density lipoprotein (LDL) and highdensity lipoprotein (HDL), and HDL/LDL ratio were the examined. The result showed that Aflatoxin Bcaused hepatotoxicosis in broiler chickens indicated by the increase of total cholesterol and LDL, and thedecrease of HDL and HDL-LDL ratio. Treatment of chickens with 2% GE decreased total cholesterol andLDL level in serum, and increased HDL level and HDL-LDL ratio. No interaction effect was observedbetween aflatoxin B and GE extract treatments. It is evident that treatment of Garlic extract reduces thehepatotoxicosis effect of aflatoxin B treatment in broiler chickens.
Keywords: aflatoxin B1, garlic extract, cholesterol, broiler